Effect of Uncaria tomentosa Extract on Apoptosis Triggered by Oxaliplatin Exposure on HT29 Cells - de Oliveira, Liliane Z. (Evid Based Complement Alternat Med, 2014)
Background/Aim. The use of herbal products as a supplement to minimize the effects of chemotherapy for cancer treatment requires further attention with respect to the activity and toxicity of chemotherapy. Uncaria tomentosa extract, which contains oxindole alkaloids, is one of these herbal products. The objective of this study was to evaluate whether Uncaria tomentosa extract modulates apoptosis induced by chemotherapy exposure. Materials and Methods. Colorectal adenocarcinoma cells (HT29 cells) were grown in the presence of oxaliplatin and/or Uncaria tomentosa extract. Results. The hydroalcoholic extract of Uncaria tomentosa enhanced chemotherapy-induced apoptosis, with an increase in the percentage of Annexin positive cells, an increase in caspase activities, and an increase of DNA fragments in culture of the neoplastic cells. Moreover, antioxidant activity may be related to apoptosis. Conclusion. Uncaria tomentosa extract has a role for cancer patients as a complementary therapy. Further studies evaluating these beneficial effects with other chemotherapy drugs are recommended.